The Role of Sociality, Entertainment, and Enjoyment in Shaping Mobile Game User Loyalty: The Mediating Effect of Flow Experience - Sinarwaty (International Journal of Accounting and Economics Studies, 2025)
The rapid development of online mobile games today requires online game developers to create high loyalty in their players to survive. This study aims to determine and analyze the role of sociality, entertainment, and enjoyment felt by online game players in influencing the level of loyalty they have, and to examine the role of flow experience as a mediator that can affect changes in loyalty. This study took a sample of 300 online mobile game players who met certain criteria as respondents in this study. Survey techniques through online questionnaires were distributed to respondents, where the data collected were then analyzed using structural equation modeling (SEM). The results of this study indicate that sociality, entertainment, as well as enjoyment and flow experience can have a positive influence on increasing loyalty owned by online game players. In addition, both entertainment, sociality, and enjoyment were also found to affect the level of flow experience felt, and flow experience was found to be a good mediator in supporting every aspect felt by online game players to be more loyal to the games played. These findings provide an understanding that to form a high level of loyalty, online mobile game service providers need to pay attention to every aspect that is the reason why players play online games.
Keywords: Mobile Game, Social Entertainment, Enjoyment Experience